Traditional Chinese Medicine in Patients With Primary Sjogren's Syndrome: A Randomized, Double-Blind, Placebo-Controlled Clinical Trial - Chen, Huang-Hsi; Lai, Jung-Nien; Yu, Min-Chien; Chen, Chia-Yin; Hsieh, Yi-Ting; Hsu, Yi-Fan; Wei, James Cheng-Chung (Frontiers in Medicine, 2021)
Background: Sjogren's syndrome (SS) is a chronic inflammatory autoimmune disease mainly characterized by dryness, fatigue, and pain. Current therapies for SS in Western medicine are limited. The purpose of this clinical study was to explore the efficacy and safety of using a traditional Chinese medicine (TCM) formula on patients with primary SS. Methods: We performed a 12-week, randomized, double-blinded, placebo-controlled clinical trial at Chung Shan Medical University Hospital. We included 42 patients with SS between the ages of 20 and 80 years who met the classification criteria of the American and European Consensus Group (AECG). Patients who had other severe systemic manifestations or diseases were excluded from this trial. After screening, patients were randomly assigned to the TCM treatment group or placebo group (ratio of 2:1). We treated the TCM group with 6 g of Gan-Lu-Yin granules after breakfast and 6 g of Jia-Wei-Xiao-Yao-San combined with 1 g of Suan-Zao-Ren-Tang and 1 g of Ye-Jiao-Teng every night after dinner. Patients in the control group were treated with a placebo with the same appearance and flavor but only one-tenth the dosage of that received by the treatment group. The European League Against Rheumatism Sjogren's Syndrome Patient-Reported Index (ESSPRI) was used as the primary endpoint at week 12. Secondary endpoints were the Sjogren's Syndrome Disease Activity Index (SSDAI), physician global assessment (PGA), visual analogue scale (VAS), Multidimensional Fatigue Inventory, Medical Outcomes Survey Short Form-36, and the Pittsburgh Sleep Quality Score (PSQI). Adverse events were also recorded. Results: Of the 42 randomized patients, 28 patients were assigned to the TCM treatment group and 14 patients were assigned to the controlled group. During the study period, 5 patients withdrew from the TCM group and 7 withdrew from the control group. At week 12, the ESSPRI scores of both groups had improved. The ESSPRI score of the treatment group decreased by 0.62 (95% CI P = 0.557) and that of the placebo group decreased by 0.91 (P = 0.557). However, no significant difference was observed between the two groups. Sleep duration in the PSQI was −0.61, which exhibited an improvement of more than the −0.21 compared with the placebo group (P = 0.914). Conclusion: At week 12, the ESSPRI scores did not reveal that the use of the TCM formula was efficacious for treating patients with Sjogren's syndrome. However, the PSQI scores indicated that this formula could prolong patient sleep duration. We also found that this formula could decrease the blood pressure of patients.